دراسة تحليلية لبعض العوامل المؤثرة في تنافسية الاقتصاد الجزائري - hadjira, Abdeljalil (Finance and Business Economies Review, 2017)
The objective of this article is to measure the impact of some macroeconomic variables of the Algerian economy such as "exchange rate, exports, income per capita, general price level, foreign direct investment, "on GDP per capita, which is used as a proxy variable of competitiveness, using a Vector Auto Regression Model (VAR), with the Granger stationary tests and analysis of the variance.